Transport characteristics of AlGaN/GaN structures for amplification of terahertz radiations - Kaur, Harpreet; Sharma, Rajesh; Laurent, T.; Torres, J.; Nouvel, P.; Palermo, C.; Varani, L.; Cordier, Y.; Chmielowska, M.; Faurie, J.-P.; Beaumont, B. (Applied physics. A, Materials science & processing, 2022)
The study of devices to amplify the terahertz (THz) radiations is a subject of intense research among the scientific community owing to its interdisciplinary applications. We explore the possibility of amplification of THz radiations by investigating the transport measurements of GaN/AlGaN structures. We investigate the transport characteristics of AlGaN/GaN high-electron-mobility transistor (HEMT), transmission lines model (TLM), and interdigitated finger (IDF) structures as functions of geometry, temperature, and operating conditions. In the transport measurements of HEMT structure at 300 K, the pulsed mode operation attains higher value of the drain current in comparison to the continuous-wave operation mode of the relatively larger geometries which is typically related to the self-heating effect. Nevertheless, the pulsed mode operation transport measurements of the relatively smaller HEMT structures overlap and attain even lower drain current values than that of the CW operation mode measurements whose origin is attributed to the trap manifestation at low temperatures. The major part of the applied voltage on the symmetric IDF structure is spread over the contacts whilst less than 10 % will effectively be applied on the channel. Moreover, the transport measurements of 5 μ m long TLM structure at 7 K show a kink at 0.1 V which is originated from the onset of the optical phonon transit time resonance mechanism. The present investigations of AlGaN/GaN structures should be helpful to obtain terahertz amplification in the electronic devices.